ANALISIS DETERMINAN TINGKAT KEMISKINAN DI PROVINSI SUMATER SELATAN PADA TAHUN 2017-2020 - Saifulloh, M Arif; Qurrota A’yun, Indanazulfa (JIDE : Journal Of International Development Economics, 2024)
Prolonged poverty will lead to complex problems. Poverty will arise when people are unable to fulfill their basic daily needs and do not reach a standard standard standard of living. Poverty will also result in economic inability to fulfill daily needs. Poverty is one of the standards for assessing the success of regional development, poverty can also cause many social problems. This study aims to analyze the effect of economic growth, unemployment, and the Human Development Index (HDI) on the poverty rate in South Sumatra Province in 20117-2020 simultaneously and partially. The research method used is panel data regression with the help of Eviews 12 software. Referring to the results of the analysis using the random effect model, simultaneously the independent variable affects the dependent variable. While partially, it was found that HDI had a negative and significant effect, economic growth had a positive and significant effect, and the unemployment rate had a negative and insignificant effect on the poverty rate.